Monsoon 2013: Estimating the impact on agriculture - Ashok Gulati; Shweta Saini; Surbhi Jain (Indian Council for Research on International Economic Relations (ICRIER), 2013)
This paper attempts to project the likely impact of robust monsoon rains of 2013 on the Agricultural Gross Domestic Product (GDP) growth in India. The model hypothesizes that the performance of agriculture in India depends upon (1) investments in agriculture (private and public); (2) agricultural price incentives; and (3) rainfall. A log-linear model fitted over 1996-97 to 2012-13 period can explain 95 percent of the variations in agri-GDP with all variables being statistically significant. The model also forecasts that the agri-GDP growth rate for the agricultural year (July-June) 2013-14 is likely to be between 5.2% and 5.7%. An alternative model to double check the results is also used. In this model, the AGCF is replaced by a simple trend variable; the idea being that the trend captures development of various investments and technologies that take place in agriculture over this period. Other variables remain the same. This model also suggests that the agri-GDP growth will be between 5.1% and 5.6%. The paper estimates that agri-GDP growth in 2013-14 is likely to be about three times higher than last year. And it is likely to come largely from oilseeds, pulses, cotton, and coarse cereals belt of central and western parts of the country, which is less irrigated and thereby more dependent on rains. It is very likely that any damage to kharif crops due to excess rainfall (with extended monsoons and cyclones) would be offset by a bumper rabi crop, given that there is excellent soil moisture and ample surplus water in reservoirs. This high growth in agri-GDP is likely to trigger a multiplier effect on manufacturing and services sectors, and thereby propel overall GDP growth rate.
Keywords: Q15; Q25; Q51; 330; Drought; Water; Agricultural and Environment; Rainfall; Contingent Valuation